Manitoban Consensual Non-monogamous Couples' Conciliation of Their Parenting Role and Their Sexual Lifestyle During the Transition to Parenthood - Avanthay Strus, Jacqueline (Université d'Ottawa / University of Ottawa, 2019)
Background: Consensual non-monogamous couples (CNMCs) are viewed less favourably than their heteromononormative counterparts by the general population and by healthcare providers. Research indicates that they are less likely to seek health care and are at greater risk for STIs and HIV. This stigma and judgment perceived by CNMCs can be even further compounded when these couples choose to have a child. No study to date has looked at consensual non-monogamous parenting couples (CNMPCs) during the transition to parenthood. The aim of the present study was to explore Manitoban CNMCs’ perceptions of the conciliation between their parenting role and their sexual lifestyle during the transition to parenthood. Methodology: This mixed methods descriptive, exploratory study used a triangulation design-convergence model. Six participants identifying as CNMCs during the transition to parenthood were interviewed using a semi-structured interview guide as well as completing an online questionnaire. Results: The participants in this sample experienced challenges in regard to their transition to parenthood as many other parents do, yet this transition was more harmonious for some participants compared to others. Consensual non-monogamy (CNM) was a sexual lifestyle chosen either before or during this transition. However, the lifestyle did stop during conception and pregnancy, and was resumed several months after childbirth. Relationship breakdown may occur, but not necessarily associated with CNM. The conciliation of parenting and sexual roles is facilitated when communication and intimacy are present between partners. Participants emphasized the importance of family before their chosen sexual lifestyle. The relationship with health care providers is critical for participants of CNM as it impacts how they seek health care or disclose their lifestyle. This is more important during the transition to parenthood as more challenges can be present. Three phases that CNMCs pass through were also identified, contemplation, acting and incorporation, to integrate CNM as a lifestyle. Discussion: These findings permitted a closer look at the conciliation of the parenting role and the sexual lifestyle of CNMPCs during their transition to parenthood. These findings demonstrated not only how CNMPCs were similar and different from participants in other studies, but also highlighted how they were uniquely distinct. This distinction appears to stem from a certain resilience gained from the three phases of the incorporation of CNM as a lifestyle that appears to buffer these couples in situations of stress. A new proposed model, CNMPCs’ Model of Resilience during the Incorporation of CNM as a Lifestyle While Parenting, is suggested. There is a need for more psychosexual education for perinatal nurses in regard to sexuality minorities such as CNMPCs in the context of the transition to parenthood.
Keywords: Consensual non-monogamy; Transition to parenthood; Conciliation of roles; Swinger; Polyamory; Open relationship; Pregancy; Childbirth; Postpartum